Penyuluhan Kesehatan Tentang Skabies Dengan Metode Diskusi Pada Santri Putri Pondok Pesantren Al-Masyrifah Palimanan Kabupaten Cirebon - Sumarmi Sumarmi; Erida Fadila (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2023)
Scabies is a skin infection caused by the Sarcoptes scabiei mite. Scabies is easily transmitted in densely populated areas such as Islamic boarding school dormitories. The aim of this community service activity is to provide health education about scabies to female students at the Al-Masyrifah Palimanan Islamic Boarding School, Cirebon. The method used is focus group discussion. A total of 40 female students were divided into 4 discussion groups. The results show an increase in students' knowledge and awareness about the symptoms, causes, modes of transmission, and efforts to prevent scabies. Interactive discussions also trigger critical questions and exchange of information between students. At the end of the session, an example of WHO's 6 steps of hand washing practice was given. It was concluded that health education through group discussions was effective in increasing female students' knowledge and awareness about scabies prevention in the Islamic boarding school environment.